Serous Surface Papillary Adenocarcinoma: a rare variant of serous carcinoma - report of two cases (Indian Journal of Case Reports, 2016)
Serous tumors constitute about 25% of all ovarian tumors. Serous adenocarcinomas are the commonest form of the malignant epithelial ovarian tumors accounting for 26% of the cases. The commonest morphologic form is the cystadenocarcinoma. Serous surface papillary adenocarcinoma is a very rare morphologic entity which is often bilateral and highly aggressive. Reports showing an exact incidence are not available in literature. We present a case of serous surface papillary adenocarcinoma confined to ovary.